1993
DOI: 10.1111/j.1365-2044.1993.tb07179.x
|View full text |Cite
|
Sign up to set email alerts
|

Near fatal pulmonary hypertension after surgical repair of congenital diaphragmatic hernia

Abstract: SummaryThe addition of 10-20 parts per million nitric oxide to the inspired gas was successful in controlling near fatal pulmonary hypertension after surgical repair of a congenital diaphragmatic hernia in a neonate. A preceding prostacyclin infusion was unable to prevent the failure of pulmonary perfusion. No side effect of nitric oxide therapy was observed, and ventilatory support could be substantially reduced as a result of the treatment. On the basis of the striking and lifesaving effects of nitric oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 23 publications
0
9
2
Order By: Relevance
“…244 Early reports demonstrated that iNO can improve oxygenation and PH in some infants with severe CDH shortly after birth. 244,245 However, 2 RCTS of iNO treatment in the first hours after birth for CDH have been reported, 206,246 showing that early iNO treatment in patients with CDH had no effect on the combined end point of death and ECMO use. 206,246 In 1 trial, ECMO use was significantly higher in the iNO-treated group.…”
Section: Pah-specific Therapymentioning
confidence: 99%
“…244 Early reports demonstrated that iNO can improve oxygenation and PH in some infants with severe CDH shortly after birth. 244,245 However, 2 RCTS of iNO treatment in the first hours after birth for CDH have been reported, 206,246 showing that early iNO treatment in patients with CDH had no effect on the combined end point of death and ECMO use. 206,246 In 1 trial, ECMO use was significantly higher in the iNO-treated group.…”
Section: Pah-specific Therapymentioning
confidence: 99%
“…The dose of NO used for these patients has been in the same dose range as in our patients with no observed adverse reactions (24, 25, 26). Successful NO administration has also been reported in one preterm infant with pulmonary vasospasm associated with respiratory distress syndrome (27) and other case reports have also described a beneficial effect of inhaled NO in neonates and children (28,29,30,31). We chose a short exposure time at each dose level based on ethical considerations and previously published experiences indicating a rapid response time to inhaled NO (30,32).…”
Section: Discussionmentioning
confidence: 99%
“…Only two case reports of clinically significant methaemoglobinaemia during inhaled NO therapy have been published. Both were in neonates, one of which was given an inadvertent overdose [30,31]. Inhaled NO has now been used in many thousands of patients in doses recommended in this document without reports of clinically significant methaemoglobinaemia.…”
Section: Background and Controversiesmentioning
confidence: 99%